2011
DOI: 10.1002/app.33498
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, dynamic mechanical, and electrical properties of bio‐based poly(trimethylene terephthalate) blends, part 1: Poly(trimethylene terephthalate)/poly(ether esteramide)/polyethylene glycol 400 bis(2‐ethylhexanoate) blends

Abstract: Bio-based PTT and PTT blends with PEEA of two different ion contents (275 ppm Na and 3515 ppm Na) and PEG 400 bis (2-ethylhexanoate) were prepared by melt processing. The blends were characterized by differential scanning calorimetry, dynamic mechanical analysis, transmission electron microscopy, and atomic force microscopy. Electro-static performance was also investigated for those PTT blends since PEEA is known as an ion conductive polymer. Here we confirmed that PEG 400 bis (2-ethylhexanoate) improves the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
2
2
0
Order By: Relevance
“…Through our attempt to reduce the T g of PEEA domain, we found polyethylene glycol 400 bis(2-ethylhexanoate) worked to reduce the T g of PEEA by melt extrusion process technique. 44 We confirmed static dissipative performance of the blends was significantly improved by reducing the T g for PEEA in the blends. We believe it is explained by enhancing the ion mobility in PEEA domains through reducing the glass transition temperature of PEEA which is an ion conductive polymer.…”
Section: Static Decay Performance Indexsupporting
confidence: 83%
See 2 more Smart Citations
“…Through our attempt to reduce the T g of PEEA domain, we found polyethylene glycol 400 bis(2-ethylhexanoate) worked to reduce the T g of PEEA by melt extrusion process technique. 44 We confirmed static dissipative performance of the blends was significantly improved by reducing the T g for PEEA in the blends. We believe it is explained by enhancing the ion mobility in PEEA domains through reducing the glass transition temperature of PEEA which is an ion conductive polymer.…”
Section: Static Decay Performance Indexsupporting
confidence: 83%
“…44 We confirmed that static dissipative performance of the blends was significantly improved by reducing the T g for PEEA in the blends. We believe it is explained by enhancing the ion mobility in PEEA domains through reducing the glass transition temperature of PEEA which is an ion conductive polymer.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…E / first decreased and reached a minimum around 70°C and then increased. This behaviour is due to a relaxation (glass transition) and cold crystallization of PTT [35]. The a relaxation temperature (T a ) of PTT was around 61°C (Fig.…”
Section: Modellingmentioning
confidence: 97%